Motivational Values of Ukrainian Students and the Use of Distance Learning Form in Legal Education - Ківалов, Сергій Васильович; Kivalov, Sergiy V.; Кивалов, Сергей Васильевич; Ківалов, С. В.; Kivalov, Sergey; Біла-Тіунова, Любов Романівна; Біла-Тіунова, Л. Р.; Била-Тиунова, Любовь Романовна; Bila-Tiunova, Liubov R.; Bila-Tiunova, Liubov (San Jose : Horizon Research Publishing, 2020)
In order to implement new national curriculums in the field of higher education in Ukraine, it is necessary to use the open educational forms as one of the sustainable development conditions. Therefore, the authors used a correlated analysis, Kolmogorov-Smirnov test, F-test, and Pearson’s chi-squared test in order to examine the Ukrainian students’ motivation towards the education according to the theory of internal motivation. The present study was based on the experiment conducted in two separate universities in Ukraine. Participants of the study were students of higher education facilities, who studied on the specialty "Law". In total, 130 students were offered to take part in the experiment and only 104 students agreed on the participation. Therefore, they completed the written consent, and data were collected by survey information. The losses were due to the absence of the students or lack of the written consents during the experiment. Thus, they voluntarily participated in the study and answered the blank anonymously. Moreover, the universe rate was within the confidence interval. In addition, authors stated that the choice between traditional and ICT (Information and Communication Technologies) based educational approaches had a serious impact on the distribution of students’ motivational values. In fact, students showed higher efficiency index while studying the law with the help of distance learning. However, participants did not believe that using the distance learning form would help them to study well and pass their exams on "4" and "5". Therefore, it is established that the whole opportunity value to pay attention to the problems interesting for students is the sole harbinger for the thesis that the study of law with the help of the distance learning form makes their education qualitative. Thus, it is argued that the Ukrainian students are motivated to study law with the help of ICT, but the value distribution is different according to gender roles. For example, males may have more benefit from the use of ICT whereas females need another point of interest to use the distance learning form to study law.

Для впровадження нових національних навчальних програм у галузі вищої освіти в Україні необхідно використовувати відкриті освітні форми як одну з умов сталого розвитку. Тому автори використовували корельований аналіз, тест Колмогорова-Смирнова, F-тест та тест Хі-квадрата Пірсона (критерій згоди Пірсона), щоб вивчити мотивацію українських студентів до навчання відповідно до теорії внутрішньої мотивації. Це дослідження базувалося на експерименті, проведеному в двох окремих університетах України. Учасниками дослідження були студенти закладів вищої освіти, які навчались за спеціальністю «Правознавство». Всього було запропоновано взяти участь в експерименті 130 студентам, і лише 104 студенти дали згоду на участь. Тому вони заповнили письмову згоду, а дані збиралися за допомогою опитування. Втрати відбулися через відсутність студентів або відсутність письмової згоди під час експерименту. Таким чином, вони добровільно взяли участь у дослідженні й анонімно відповіли на бланк. Більше того, середній коефіцієнт знаходився в межах довірчого інтервалу. Крім того, автори заявили, що вибір між традиційними освітніми підходами та ІКТ (Інформаційно-комунікаційними технологіями), мав серйозний вплив на розподіл мотиваційних цінностей здобувачів освіти. Фактично студенти показали вищий показник ефективності під час вивчення закону за допомогою дистанційного навчання. Однак учасники не вірили, що використання форми дистанційного навчання допоможе їм добре вчитися та здавати їх іспити на "4" та "5". Отже, встановлено, що загальна цінність звернення уваги на цікаві для студентів проблеми є єдиним передвісником тези, що вивчення права за допомогою форми дистанційного навчання робить їх освіту якісною. Таким чином, стверджується, що українські студенти вмотивовані вивчати право за допомогою ІКТ, але розподіл цінностей різний та залежить від гендерних ролей. Наприклад, чоловіки можуть отримати більше користі від використання ІКТ, тоді як жінки мають іншу точку зору щодо використовання форми дистанційного навчання для вивчення права.

Для внедрения новых национальных учебных программ в области высшего образования в Украине необходимо использовать открытые образовательные формы как одно из условий устойчивого развития. Поэтому авторы использовали коррелированный анализ, тест Колмогорова-Смирнова, F-тест и тест Хі-квадрата Пирсона (критерий согласия Пирсона), чтобы изучить мотивацию украинских студентов к обучению согласно теории внутренней мотивации. Это исследование базировалось на опыте, проведенном в двух отдельных университетах Украины. Участниками исследования были студенты высших учебных заведений, которые учились по специальности «Правоведение». Всего было предложено принять участие в эксперименте 130 студентам, и только 104 студента дали согласие на участие. Поэтому они заполнили письменное согласие, а данные собирались с помощью опроса. Потери произошли из-за отсутствия студентов или отсутствия письменного согласия во время эксперимента. Таким образом, они добровольно приняли участие в исследовании и анонимно ответили на бланк. Более того, средний коэффициент находился в пределах доверительного интервала. Кроме того, авторы заявили, что выбор между традиционными образовательными подходами и ИКТ (Информационно-коммуникационными технологиями), имел серьезное влияние на распределение мотивационных ценностей обучающихся. Фактически студенты показали высокий показатель эффективности при изучении права с помощью дистанционного обучения. Однако участники не верили, что использование формы дистанционного обучения поможет им хорошо учиться и сдавать их экзамены на «4» и «5». Итак, установлено, что общая ценность обращения внимания на интересующие студентов проблемы является единственным предвещающим фактором положения о том, что изучение права с помощью формы дистанционного обучения делает их образование качественным. Таким образом, утверждается, что украинские студенты мотивированы изучать право с помощью ИКТ, но распределение ценностей разный и зависит от гендерных ролей. Например, мужчины могут получить больше пользы от использования ИКТ, тогда как женщины имеют другую точку зрения в отношении использования формы дистанционного обучения для изучения права.
Kivalov S. Motivational Values of Ukrainian Students and the Use of Distance Learning Form in Legal Education / S. Kivalov, L. Bila-Tiunova // Universal Journal of Educational Research. - V. 8(1). - San Jose : Horizon Research Publishing, 2020. - P. 260-283.
Keywords: Distance Learning; Higher Education; ICT; Internal Motivation Theory; Law; Ukraine; дистанційне навчання; вища освіта; ІКТ; теорія внутрішньої мотивації; право; Україна; дистанционное обучение; высшее образование; ИКТ; теория внутренней мотивации; право; Украина; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education